Implementasi Diversi Dalam Sistem Peradilan Pidana Anak Di Polres Gowa - Burhan, Burhan (Al-Hikmah, 2019)
The research was conducted and aimed at: 1) To find out the implementation of the application of diversion in the juvenile justice system at the Gowa Regional Police Station; 2) To find out and analyze what factors are the obstacles in the application of diversion to children who face huku at the Gowa Police Station. This type of research is empirical legal research, namely legal research that examines the implementation or implementation of positive legal provisions (legislation) factually on any particular legal event that occurs in society. The legal material used consists of primary legal data and secondary legal data. Techniques for collecting legal data are collected through literature studies and field studies. Then the technique for analyzing with qualitative analysis techniques by sorting and selecting, classifying, and connecting the realities that occur in the field with the problems studied, so as to provide a clear picture of what happened in the field so that it comes to a conclusion. The results showed that: 1) The application of diversion to children facing the law at the Gowa police station had been carried out financially, it was seen from the cases of children facing the law handled since 2017 until 2019 there were 94 cases and could be resolved diversely. 93 cases; 2) The inhibiting factor in the application of diversion in the Gowa Regional Police Station is that the legal factor only gives a 30-day time limit for diversion efforts, the investigator's resource factor is still lacking when compared to the number of cases handled. Community factors that sometimes do not want peace or requests from the victims or the families of victims who ask for compensation that is too large so the perpetrators cannot.